Studi Epidemiologi Dengan Pendekatan Analisis Spasial Terhadap Faktor-Faktor Risiko Penyakit Infeksi Saluran Pernapasan Akut (ISPA) Pada Anak Di Kecamatan Sragen - Wiwik Setyaningsih; Dodiet Aditya Setyawan; Ari Sarwanto (Jurnal Keterapian Fisik, 2016)
Abstract : Geographic Information System (GIS), acute respiratory infection in children. Manifestation quality healthy environment is an essential part that can not be abandoned in the field of health. Air as an important environmental component in the life of mankind, should be maintained and enhanced so as to provide carrying capacity for a higher quality of human life. Today the disease based on environment is still a health problem that is dominant in the middle - the middle of the Indonesian people. This is reflected in the high number of events and visits patients with several diseases to the center - the center of health care such as diarrhea, malaria, dengue hemorrhagic fever (DHF), tuberculosis, acute respiratory infections, skin diseases, worm infection as well as health problems or poisoning from chemicals and pesticides (Depkes RI, 2002). From these diseases, Acute Respiratory Infections still contributed the most to the morbidity, and until now the disease is still a public health problem that is the main, both in developed countries and countries emerging (Wahyudi, 2004). This study design is modeling Case Control using Geographic Information System (GIS). Purposive sample taken with the number of 80 respondents. Data were analyzed using Chi Square, Multiple Logistic Regression and spatial analysis using overlay function and Buffering. Results show risk factors are shown to be significantly associated with the incidence of respiratory disease in children in the district of Sragen is the density of the household (OR = 0.075, 95% CI = 0019-0293, with a value of p = 0.000); distance of residence to the highway within a radius of ≤ 250 meters (OR = 0334, 95% CI = 0118 to 0949, with a value of p = 0.040).